The Development of Math Learning Media: 3-Dimensional Snake and Ladder - Chusna, Puji Asmaul; Inayati, Isna Nurul; Santoso, M. Jamal Hadi (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article is motivated by the lack of mathematics learning media at Islamic primary education, which has an impact on the low motivation of students to learn the subject. To solve these problems, the development of three-dimensional snakes and ladders is an interesting thing to do. In order to develop the media and measure the feasibility of 3D snakes and ladders learning media in the mathematics subject matter of counting operations of whole numbers, this research is to be carried out. The research method used is research and development using the Borg & Gall model, which is composed of five stages that have been limited. The research subjects were homeroom teachers and fourth grade students at MI Miftaul Huda Kanigoro Blitar. By conducting validation tests with media experts, materials, math teachers, and students. So that the percentage of feasibility of material experts (79.3%) with the predicate "valid" is not revised, media experts (94.1%) with the predicate "very valid" is not revised, math teachers (92.8%) with the predicate "very valid" is not revised, and the increase in learning outcomes reaches 90%. So it is concluded that the learning media for the 3D snakes and ladders game of counting operations for small numbers reaches a value of more than 68%; therefore, it can be stated that the media is relevant or suitable for use.